High Gain Cascaded Two-Stage Low Noise Amplifier Design Using T-Matching Stub Resonator - Rusdiyanto, Dian; Adhiyoga, Yohanes Galih; Mahendra, Adhi; Aji, Arie Pangesti (Universitas Indonesia, 2024)
The capability improvement of a telecommunications device influences the performance aspect of the device. In order to access the signal source, repeaters are required to reach signal to subscribers or improvements to the user's device itself that are able to reach signals that are far away. One of the telecommunications devices on the user side includes a low noise amplifier (LNA) which is useful for strengthening the signals and reducing the noise level received. This equipment supports to stay within reach of small signals received by users in areas with less signal. In this research, LNA is discussed specifically, especially increasing LNA gain and impedance matching methods through resonator modification. The LNA is designed using a two-stage cascading method which has high gain and low reflection factor. The simulation results show that the proposed LNA design succeeded in obtaining a gain of 31.6 dB where the stability and noise figure values obtained 3.79 dB and I.87 dB respectively. The T-Matching stub method used to adjust input and output impedance also succeeded in having a low reflection coefficient. At a frequency of 1575 MHz, the input and output reflection coefficients were obtained -70.5 dB and 56.2 dB. LNA design is divided into three steps, such as LNA bias design, single-stage LNA and cascaded connected two-stage LNA. The simulation results show that the LNA design meets the agreement with the desired target specifications.